Studies of Bacterial Stalk Rot Disease of CornI - Abdullah, Hiryati (1982)
Bacterial stalk rot of corn (Zea mays L.) was observed and the causal bacterium isolated from infected corn plants. Based on the symptoms, pathogenicjty, cultural, biochemical and physiological studies, the pathogen was identified as Erwinia chrysanthemi Burk., McFadded and Dimock. However, the corn strains were found to be only weakly virulent to the susceptible pineapple cultivars tested, suggesting that it may be a distinct pathovar of the bacterium. Pathogenicity test showed that the 3 wk. and 5 wk. old corn plants, of a popular corn variety, Metro, and a recent sweet corn variety, 'Bakti', grown in Malaysia, were susceptible to the disease.